The Use of Genetic Algorithms to Determine the Optimum Duration of the Construction Project of the Gedung Fakultas Ilmu Kesehatan, Brawijaya University, Malang: Penggunaan Algoritma Genetika Untuk Penentuan Durasi Optimum Pada Proyek Pembangunan Gedung Fakultas Ilmu Kesehatan Universitas Brawijaya Malang - Yulianto, Achmad; Eko Prasetyo (Universitas Negeri Surabaya, 2025)
Genetic algorithms are used to determine the best duration for each activity in the project so as to produce the optimum duration, namely the project duration that produces the minimum total project cost. This study determine the optimum project duration and the minimum Total Project Cost in the Faculty of Health Sciences Building Construction project, Brawijaya University. Secondary data were obtained from PT Citra Mandiri Cipta as the contractor. The initial population is formed from 16 chromosomes, each chromosome contains 57 genes, each gene contains data on the duration of each activity obtained randomly. Each chromosome provides information about the duration and total cost of the project using the PDM calculation. The relationship between fitness and total project cost is that the lower the total project cost, the greater the fitness value. To produce a better fitness value, crossover and mutation are carried out in each cycle (generation). After 500 generations of repetition, the optimum duration was obtained at 238 days and the total project cost was Rp 36,653,132,882.00, resulting in cost savings of Rp22,397,054 and a duration acceleration of 7 days. The total project cost and optimum duration with the Time Cost Trade Off calculation gave the same results.